Microglial Phenotypic Transition: Signaling Pathways and Influencing Modulators Involved in Regulation in Central Nervous System Diseases - Li, Jiaxin; Shui, Xinyu; Sun, Ruizheng; Wan, Lily; Zhang, Boxin; Xiao, Bo; Luo, Zhaohui (Frontiers in Cellular Neuroscience, 2021)
Microglia are macrophages that reside in the central nervous system (CNS) and belong to the innate immune system. Moreover, they are crucially involved in CNS development, maturation, and aging; further, they are closely associated with neurons. In normal conditions, microglia remain in a static state. Upon trauma or lesion occurrence, microglia can be activated and subsequently polarized into the pro-inflammatory or anti-inflammatory phenotype. The phenotypic transition is regulated by numerous modulators. This review focus on the literature regarding the modulators and signaling pathways involved in regulating the microglial phenotypic transition, which are rarely mentioned in other reviews. Hence, this review provides molecular insights into the microglial phenotypic transition, which could be a potential therapeutic target for neuroinflammation.